Peningkatan Keterampilan Menulis Puisi Bebas dengan Menggunakan Pendekatan Kontekstual Siswa Sekolah Dasar - Putri Hana Pebriana (Publikasi Pendidikan, 2017)
The purpose of this study is to describe the planning, implementation and results of free poetry writing skills in the Indonesian language class V SDN 004 Bangkinang with Contextual Approach. This research uses qualitative method of Type Class Action Research. Data obtained in the analysis using qualitative and quantitative data analysis. Stages of data analysis are described as follows: reviewing the data that has been collected either through observation, rectification, recording, or documentation, data reduction, presenting data and concluding the research results. The results of research after done on the cycle I skill of writing free poetry with a perspecage of 59.09%. Then cycle II of free poetry writing skills has increased with the percentage of 86.36%. Teacher activity in the first cycle of the first meeting of 65.71% and at the second meeting increased to 74.28%. Then in cycle II the first meeting of teacher activity increased to 82.85% and at the second meeting increased to 88.57% ". Student activity on first cycle of the first meeting of 62.85% and at the second meeting increased to 68.57% with the category of "Good". Then in cycle II the first meeting of teacher activity increased to 77.14% and at the second meeting increased to 85.71%. Thus it can be concluded that by using Contextual Approach Can Increase the Skill of writing poetry free Student Class V SDN 004 Bangkinang district Bangkinang City.Keyword: Contextual Approach, Skill Writing, Free Poem